Inibidores de poligalacturonase (PGIPs) oriundos do feijão: produção recombinante e estudos funcionais - Peccin, Heloisa Tavoni Longhim (Universidade Federal de São Carlos, 2019)
Pectic substances are components of the middle lamella of the plant cell wall and are composed of partially methyl-esterified galacturonic acid residues linked by α-1,4 glycosidic bonds. These substances are naturally degraded by pectinases, such as the endopolygalacturonase (PG), which is responsible for the reaction of hydrolysis of α- (1,4) bonds of pectin. Pectinases and other enzymes responsible for cell wall degradation (PCWDEs) have been extensively studied in plants, bacteria, fungi and insects. As a defense strategy, the plants try to inhibit their enzymatic activity by producing inhibitors of PG, the PGIPs (Polygalacturonase Inhibitor Protein). PGIPs have a structure formed by leucine-rich repeats (LRRs), which are arranged to form two β-sheets, being that β1-sheet contains residues crucial for interaction with PGs. The high level of PGIP expression does not prevent infection, however, it significantly limits colonization of the tissue by the invading organism. Among the most studied PGIPs are polygalacturonase inhibitors from the bean (Phaseolus vulgaris), which consist of a family of 4 clustered genes (pvpgip1, pvpgi2, pvpgi3 and pvpgi4). Due to the application of pectinases in several industrial fields and to the importance of these inhibitors, the PvPGIP2 and PvPGIP3, inhibitors of the beans were recombinantly produced in Pichia pastoris, which were subjected to functional assays. Partial inhibition of Aspergillus niger pectinase activity against recombinant proteins PvPGIP2 and PvPGIP3 were observed. In addition, PvPGIP2 partially inhibited the activity of the Neosartorya glaba´s fungus pectinase for the first time reported in the literature. The recombinant proteins were also tested against pectinase of the insect Sphenophorus levis (Sl-EndoPG), but the activity of the same was not reduced.
Polygalacturonase Inhibitors (PGIPs) from bean: recombinant production and functional studies
Keywords: Inibidores de poligalacturonase; Pectinase; Pectina; Polygalacturonase Inhibitors; Pectinase; Pectin; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS